Brazilian Red-Eyed Fly Ormia depleta (Wiedemann) (Diptera: Tachinidae) - Haleigh A. Ray; Jennifer Lynn Gillett-Kaufman (EDIS, 2018)
The Brazilian red-eyed fly, Ormia depleta, is a tachinid fly that is a parasitoid of mole crickets in the genus Neoscapteriscus (Orthoptera: Gryllotalpidae). Originally from South America, it was brought to the United States for biological control of pest mole crickets. It is now established in almost all counties in central and southern Florida. Includes: Introduction - Distribution - Description - Life Cycle - Pest Management - Selected References.